Penggunaan Benzylaminopurine (BAP) dalam Mempertahankan Kualitas Bunga Potong Anggrek (Vanda douglas. Joaqium ) - Irwan Lovadi, Dwi Saptorini, Riza Linda (Universitas Tanjungpura, 2015)
The increase in the vaselife is one of the important factors to improve the quality of cut flowers of orchid Vanda douglas one of which is by giving a growth substance. The purpose of this research is to examine the influence of BAP and to find the concentration to reduce decrease of vase life and withered petals as well as maintaining the period of vase life. This research was conducted in the Biology Laboratory of the Faculty of Mathematics and Natural Sciences of the Tanjungpura University, Pontianak in May 2014. The research methods used was the Completely Randomized Design (CRD) consisting of 6 BAP concentration treatments, i.e. aquades control of 10, 20, 30, 40 and 50 ppm respectively. The results showed that the giving BAP of 20 ppm could slow down the decrease of vase life in cut flowers by 35,31%, the number of withered petals by 40% and retained the period of vase life of cut flowers up to 12,33 days.